Students' perception on the use of free writing in overcoming writing anxiety / Nor Afifa Nordin, Nursyafiqah Zabidin and Puteri Nur Hidayah Kamaludin - Nordin, Nor Afifa; Zabidin, Nursyafiqah; Kamaludin, Puteri Nur Hidayah (Universiti Teknologi MARA, Cawangan Melaka, 2019)
Writing is believed to be one of the most challenging skills to be acquired among students especially second language learners. They then develop writing anxiety which eventually leads to poor writing performance. Various teaching methodologies have been implemented to reduce students' writing anxiety. One teaching strategy that can be applied is free writing as a pre-writing activity. In this study, the instructor introduced free writing to examine students' perceptions on their writing anxiety. Thus, this paper aimed to explore students' perceptions on using free writing as a pre-writing activity in helping them cope with their anxiety while completing writing tasks. A quantitative study was conducted among Diploma students in UiTM Melaka using a free writing task given as pre-writing activity to 68 students. A questionnaire was also used for the research to assess their perceptions towards free writing. The study revealed that the respondents were most anxious when their written works would be graded. On the other hand, the questionnaire also indicated that free writing generally had a positive influence in reducing writing anxiety among the participants.